Design Model of Subak Smart Irrigation - Wijaya, Ananta; Peling, Adisimakrisna; Janardana, I Gusti Ngurah (International Journal of Engineering and Emerging Technology, 2017)
Water has  many benefits for human life. One of the benefits lies on the agricultural  sector. However,  as the water source is decreasing, the needs of water for agricultural  sector is increasing. Subak is therefore one of the solutions in agricultural  field. Meanwhile,  the existence of subak also rises  some problems. In terms  of water source management, subak can be very effective. Unfortunately, subak is not that efficient in the water use. Smart  irrigation with fuzzy logic used becomes a solution  which has  been offered to manage the water use  based on the needs the paddy.  This system uses solar panel  and battery.  In addition,  it is completed by the weather censor and humidity. This system works during rice planting period.  The findings show that the water irrigation on subak rice field becomes more effective,  efficient and optimizing the harvest.